Collaborative Governance Program of the Local Goverment of Jambi Province in an Effort to Tackle Inflation in 2022 - Hapsa; Alva Beriansyah (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2024)
This study analyzes the collaborative governance approach applied by the Jambi Provincial Government in an effort to tackle inflation in 2022, where as of July 2022 President Jokowidodo said that Jambi Province was the province that experienced the highest inflation in Indonesia, which was 8.55% and Jambi City was the city district that contributed to the highest inflation with an inflation value of 8.55% and was the highest inflation for the Regency or City level in Indonesia. Therefore, a collaborative governance approach is appropriate to see a framework that involves various stakeholders in Jambi City in overcoming inflation, including the government, private sector, academics, and the community, in the decision- making process and policy implementation. Through the formation of the Regional Inflation Control Team (TPID), the Jambi City Government managed to integrate various resources and expertise to overcome inflation caused by various factors, such as rising prices of basic commodities and distribution disruptions, seen in early 2023 the Jambi City inflation rate began to stabilize. The method used is a qualitative approach, by describing the extent of the collaborative process carried out, and is inductive, this is because the data obtained is then developed into basic assumptions from informants, then followed up repeatedly so that it can be concluded that these assumptions can be accounted for. The stages of collaboration start from problem identification and goal setting, the formation of collaborative structures, the development of action plans, to the implementation of strategic policies and programs. Regular monitoring and regular evaluations are carried out to assess the effectiveness of the steps taken, followed by a strategy program based on the results of the evaluation with the stakeholders involved such as the market operation program, the 'Payo menanan chili' movement, UMKM assistance, and the local rice purchase program, all of these programs require active community participation and public education as an important component in maintaining price stability and managing inflation expectations in Jambi City. The results showed that the collaborative governance approach applied by the Jambi City Government was effective in tackling inflation and maintaining price stability as evidenced by the decline in the inflation index to 1.96% from the previous 8.55% highest in the nation. These findings can serve as a model for other regions in facing similar economic challenges.